(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Aim: The major objective of this proposed work is to evaluate the PV-powered buck-boost converter when differentiated from the Boost converter that will make the most efficient use of renewable energy. As a result, this research on the generation and enhancing power flow using a buck-boost converter is presented. Materials and Methods: PV system interfaced with a Boost converter and Buck-Boost converter is analyzed. The sample size is calculated as 14 with each group as 7 using GPower software. The significance value is determined as 0.001 (p<0.05) based on SPSS analysis. Results: Buck-Boost converter provides an efficiency of 49.78% whereas the conventional Boost converter has 39.41%. The significance value is determined as 0.001 (p<0.05, statistically significant) based on SPSS analysis. Conclusion: PV-powered buck-boost converter gives more efficiency at a faster pace under varied operating conditions. As a result, this will be a superior platform for generating power and satisfying load demands.